Reputation building, website disclosure and the case of intellectual capital - Abesekera, Indra (Studies in managerial and financial accounting ;, 2010)
This study investigated the following aspects of the 100 most entrepreneurial firms more widely known as the fastest growing firms in Australia. Firstly, the study analysed the association between intellectual capital disclosure types (narrative, visual, and numerical) on company-sponsored websites, using content analysis, and the corporate growth aspect of reputation of these firms over a three-year period from 2005 to 2007. Secondly, the study investigated the perceptions of directors about the value relevance of intellectual capital resource items in enhancing corporate reputation. Thirdly, the study identified motivations behind the extent of intellectual capital resource items disclosure on company-sponsored websites when the director perception survey was inconsistent with such disclosures.